Overcoming Vulnerability of Unemployment Insurance Schemes - Pareliussen, Jon (OECD Publishing, 2014)
Unemployment insurance is a key tool for risk sharing and redistribution and also a prominent automatic stabiliser. It is a volatile spending item by design, which can lead to vulnerabilities. This paper explores various shocks and sources of vulnerability of the unemployment insurance schemes of OECD and BRIICS countries. Policies that boost both financial resilience and benefit adequacy as well as policy trade-offs are explored. Four country clusters are identified with key similarities in the overall policy mix that can shed light on why some countries boast generous benefits and at the same time display high economic efficiency, while other countries face a much more pronounced trade-off
Keywords: Employment; Economics